A4.07 IL-22 impact on human bone marrow mesenchymal stem cells functions; a unique pathway that may contribute to aberrant new bone formation in human SPA. (24th February 2016) - El-Sherbiny, YM; El-Zayadi, A; Cuthbert, R; Baboolal, T; Fragkakis, A; Jones, E; McGonagle, D
Abstract : Background and objectives: The human spondyloarthropathies (SpA) are associated with single nucleotide polymorphisms (SNPs) in the IL-23 pathway and IL-23/17 axis therapy is effective in SpA. The SpAs are also associated with new bone formation that is to a degree independent of TNF blockade. Given that IL-23R receptor signalling in lymphoid cells is associated with IL-22 production and since IL-22 is a pivotal cytokine that maintains gut and skin stem cell function, 1, 2 we hypothesised that IL-22 might also drive skeletal stem cells and hence contribute to the SpA bone phenotype. Therefore we explored the effect of IL-22 on bone marrow mesenchymal stem cells (MSCs). Materials and methods: Human Bone marrow MSCs were expanded and tested by flow cytometry for IL-22R expression. MSC proliferation and migration were tested by colorimetric XTT assay and chamber migration assays. MSC osteogenic functional differentiation was performed with and without cytokines. Results: MSCs expressed low level IL22RA1 which was significantly up-regulated (1.8 ± 0.12 fold) in combination with IFNG and TNFa. MSCs proliferation and migration dramatically increased following IL-22 exposure after IFNG and TNFa combined priming compared to IL-22 alone or no cytokine. MSCs migration function was enhanced by IL-22 after priming with IFNG and TNFa compared to no cytokine. Osteogenic differentiation was significantly higher in MSCs exposed to IL-22 alone, but decreased when IL-22 combined with IFNG and TNFa. Conclusion: IL-22 is exclusively produced by immune cells and acts on non-immune cells including stem cells; our findings confirm that IL-22 can drive bone marrow MSC osteogenesis. Furthermore, IL-22 boosted MSCs proliferation and migration after priming with IFNG & TNFa in vitro and had variable effects depending on the inflammatory milieu. Given that the IL-23 axis association with SpA this work opens up a novel pathway for exploring new bone formation in SpA related disease. References: Eyerich et al. J Clin Invest. 2009;119(12):3573–3585 Serafini et al . J Exp Med. 2014;211(2):199–208